2019
DOI: 10.9734/bji/2018/v22i330060
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Studies on Isolation, Bile Tolerance and Antibiogram of Potential Probiotics (Probionts) from Locally Fermented Food Products at Beach Market, Nsukka Metropolis, Enugu State, Nigeria

Abstract: Aims: The study aims to isolate, evaluate bile tolerance and antibiogram studies of potential probiotics (Lactobacillus spp) from locally fermented Food Products (Akamu, Aqua Rafa® Yoghurt, Ogiri, Okpeye) and Kunu at Beach Market, Nsukka. Study Design: A ten - fold serial dilution and spread plate method using De Man, Rogosa and Sharpe (MRS) medium was adopted for isolation of potential Probionts. Place and Duration of Study: Department of Pharmaceutical Microbiology and Biotechnology, Faculty of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…These findings also show that antibiotic resistance varies from study to study due to differences in experimental conditions like broth used. The lack of standard methods to test antibiotic susceptibility of candidate probiotic bacteria is the reason why some LAB strains reported to harbour tetracycline-or erythromycinresistant patterns, as in our results, later turned out to be negative for the resistance tet (M) or erm (B) genes (Berebon et al, 2018;Bertel et al, 2019). This could occur because the microbial community of BC underwent different ecological succession processes in the tests carried out.…”
Section: Discussionmentioning
confidence: 65%
“…These findings also show that antibiotic resistance varies from study to study due to differences in experimental conditions like broth used. The lack of standard methods to test antibiotic susceptibility of candidate probiotic bacteria is the reason why some LAB strains reported to harbour tetracycline-or erythromycinresistant patterns, as in our results, later turned out to be negative for the resistance tet (M) or erm (B) genes (Berebon et al, 2018;Bertel et al, 2019). This could occur because the microbial community of BC underwent different ecological succession processes in the tests carried out.…”
Section: Discussionmentioning
confidence: 65%
“…A tenfold serial dilution and a spread plate method was used as reported in previous study (Berebon et al, 2019). Based on visual examination a distinct colony was picked with a sterile wire loop and transferring aseptically into a sterile MRS agar plate by quadrant streak method.…”
Section: Isolation Of Potential Lactic Acid Bacteriamentioning
confidence: 99%
“…Probiotics as well as their bacteriocins (produced by some probiotic organisms) are considered to substitute for antibiotics in the food and pharmaceutical sector. Lactic acid bacteria (LAB), commonly regarded as the major group of probiotic bacteria, are rods or cocci, facultative anaerobes, belong to the non-spore forming firmicutes groups with low Guanine (G) and cytosine (C) -G + C (< 50%) with members belonging to the genera -Enterococci, Lactobacillus, Lactococcus, Leuconostoc, Pediococcus and Streptococcus (Berebon et al, 2019). There are stringent selection criteria for the development of commercial probiotics.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that some strains of lactic acid bacteria (LAB) isolated from fermented foods display attributes desirable for probiotic cultures [16]. In Nigeria, probiotics have been isolated from different fermented foods [7,17,18,19,20,8]. However, the criteria for LAB strains to be characterised as probiotics either for food or nutraceutical applications are constantly evolving and developing.…”
Section: Introductionmentioning
confidence: 99%